The association of type and number of high-risk criteria with cancer-specific mortality in prostate cancer patients treated with radical prostatectomy - Chierigo, Francesco; Flammia, Rocco Simone; Sorce, Gabriele; Hoeh, Benedikt; Hohenhorst, Lukas; Panunzio, Andrea; Tian, Zhe; Saad, Fred; Graefen, Marcus; Gallucci, Michele; Briganti, Alberto; Montorsi, Francesco; et al. (Current urology, 2024)
OBJECTIVES: This study aimed to test the association between of type and number of D'Amico high-risk criteria (DHRCs) with cancer-specific mortality (CSM) in high-risk prostate cancer patients treated with radical prostatectomy. MATERIALS AND METHODS: In the Surveillance, Epidemiology, and End Results database (2004-2016), we identified 31,281 radical prostatectomy patients with at least 1 DHRC, namely, prostate-specific antigen (PSA) >20 ng/mL (hrPSA), biopsy Gleason Grade Group (hrGGG) score of 4 and 5, or clinical tumor stage ≥T3 (hrcT). Multivariable Cox regression models and competing risks regression models (adjusting for other cause mortality) tested the association between DHRCs and 5-year CSM. RESULTS: Of 31,281 patients, 14,394 (67%) exclusively harbored hrGGG, 3189 (15%) harbored hrPSA, and 1781 (8.2%) harbored hrcT. Only 2132 patients (6.8%) harbored a combination of the 2 DHRCs, and 138 (0.6%) had all 3 DHRCs. Five-year CSM rates ranged from 0.9% to 3.0% when any individual DHRC was present (hrcT, hrPSA, and hrGGG, in that order), 1.6% to 5.9% when 2 DHRCs were present (hrPSA-hrcT, hrcT-hrGGG, and hrPSA-hrGGG, in that order), and 8.1% when all 3 DHRCs were present. Cox regression models and competing risks regression confirmed the independent predictor status of DHRCs for 5-year CSM that was observed in univariable analyses, with hazard ratios from 1.00 to 2.83 for 1 DHRC, 2.35 to 5.88 for combinations of 2 DHRCs, and 7.13 for all 3 DHRCs. CONCLUSIONS: Within individual DHRCs, hrcT and hrPSA exhibited weaker effects than hrGGG did. Moreover, a dose-response effect was identified according to the number of DHRCs. Accordingly, the type and number of DHRCs allow further risk stratification within the high-risk subgroup.
Keywords: SEER; High risk prostate cancer; Cancer-specific mortality; Staging; Radical prostatectomy